Successful Live Related Renal Transplantation in a 13 year old girl complicated with limited vascular access and fungal infections: A Case Report. - Muhammad Tassaduq Khan; Sidra Rashid; Rashid bin Hamid (Liaquat Medical Research Journal)
This case report illustrates a 13-year-old girl, a known case of hypertension (HTN) and End Stage Renal Disease (ESRD) secondary to Lupus nephritis (biopsy proven), who was commenced on maintenance hemodialysis twice weekly since two months. No permanent access was formed in the meantime as she had complicated vascular anatomy and multiple attempts leading to thrombosis. Arteriovenous Fistula (AVF) formation carried high risk of thrombosis, as well as the central access for hemodialysis was unattainable for long term use. She was admitted with central line bloodstream infection (CLABSI) and pneumonia which was non-responsive to IV antibiotics, her fungal markers showed elevated Galactomannan and beta D Glucan levels. These high levels necessitated the initiation of anti-fungal therapy and Voriconazole was started, which was later switched to Amphotericin B and Isavuconazole as no response was observed in earlier treatment. She underwent successful renal transplantation while her antifungal treatment was underway. This case reports a lifesaving transplant in a septic patient with limited central access for hemodialysis.